Numerical modeling of Subthreshold region of junctionless double surrounding gate MOSFET (JLDSG). (February 2016) - Rewari, Sonam; Haldar, Subhasis; Nath, Vandana; Deswal, S.S.; Gupta, R.S.
Abstract: In this paper, Numerical Model for Electric Potential, Subthreshold Current and Subthreshold Swing for Junctionless Double Surrounding Gate(JLDSG) MOSFEThas been developed using superposition method. The results have also been evaluated for different silicon film thickness, oxide film thickness and channel length. The numerical results so obtained are in good agreement with the simulated data. Also, the results of JLDSG MOSFET have been compared with the conventional Junctionless Surrounding Gate (JLSG) MOSFET and it is observed that JLDSG MOSFET has improved drain currents, transconductance, outputconductance, Transconductance Generation Factor (TGF) and Subthreshold Slope. Highlights: Subthreshold Analytical Model for Junctionless Double Surrounding Gate (JLDSG) MOSFET. Improved Drain Currents, Transconductance, Transconductance generation factor and Subthreshold Slope. Applicable to Analog Appications.